Resistance of Tribofium castaneum to Phosphine and the Relationship between Complete Lethal Concentration and Exposure Time of Phosphine in Hainan Province - Chen Yan Zhang Hongjian Xie Gengxiang Zhao Kuo Luo Shan Wang Tao Zheng Lianhe (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
[Objeetive] The paper was to investigate the resistance of Tribolium castaneum to phosphine in Hainan Province. [Method] Using the measurement method of phosphine resistance of stored grain pests recommended by FAO, the phosphine resistance of eight strains of T. castaneum adults in Hainan Province was determined. [Result] The resistance coefficients of different strains of ？7. castaneum against phosphine ranged from 612 to 1 045, and all strains reached extremely high resistance level （Rf〉 160）. When the concentration of phosphine was 200 mL/m^3, Rf612, Rf826.4 and Rfl 045 strains had complete lethal time of 8, 9 and 11 d, respectively. [Condusion] T. castarveum in Hainan Province had very strong resistance to phosphine, and the operation scheme of low concentration and long duration should be adopted in elimination of T. castaneum.